1979
DOI: 10.1037/h0081713
|View full text |Cite
|
Sign up to set email alerts
|

Melody recognition: The experimental application of musical rules.

Abstract: Recognition of a transposed sequence of three tones was tested under four conditions of tone context. The melodic sequence was presented either without context or embedded in one of three types of context that varied according to the number of musical rules applied in their derivation. The recognition test (two-alternative forced choice) involved detection of a shift of one semit of one tone of the sequence, the shift being to a tone either within or without the musical key of the sequence. In addition, the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 17 publications
10
127
0
Order By: Relevance
“…As already discussed, previous research has demonstrated that musical tonality has a significant impact on memory, with tonal melodies better remembered than atonal melodies (Cuddy et al, 1981;Cuddy et al,, 1979;Frances, 1988). Although the melodies employed in this experiment were all tonal, the randomization procedure creating the different variants of each melody did produce differences between the variants in the total durations of the notes of these melodies.…”
Section: Memory Performance and Musical Tonalitymentioning
confidence: 82%
See 1 more Smart Citation
“…As already discussed, previous research has demonstrated that musical tonality has a significant impact on memory, with tonal melodies better remembered than atonal melodies (Cuddy et al, 1981;Cuddy et al,, 1979;Frances, 1988). Although the melodies employed in this experiment were all tonal, the randomization procedure creating the different variants of each melody did produce differences between the variants in the total durations of the notes of these melodies.…”
Section: Memory Performance and Musical Tonalitymentioning
confidence: 82%
“…For example, research has shown that memory for tonal melodies is better than memory for atonal melodies (Cuddy, Cohen, & Mewhort, 1981;Cuddy, Cohen, & Miller, 1979;Frances, 1988). .…”
mentioning
confidence: 99%
“…Although we have derived tonal magnitude as a power transformation of the standardized key profile, on reflection it is clear that tonal magnitude is in many ways comparable to the more familiar concept of tonal strength. Research on tonal strength has occupied a central place in work on musical cognition, with such investigations extensively studying, for example, the consequences of varying tonal strength on the processing of and memory for musical passages (e.g., Croonen, 1994Croonen, , 1995Cuddy, Cohen, & Mewhort, 1981;Cuddy, Cohen, & Miller, 1979;Cuddy & Lyons, 1981;Dowling, 1978Dowling, , 1991. In addition, this work has identified characteristics that make a passage tonally strong, with music heard as tonally strong if it (a) is diatonic, in that it is composed primarily of pitches of the diatonic set; (b) begins and ends on the tonic; and (c) exhibits cadential structure (e.g., contains a sequence of chords built on Pitch Class 0, followed by Pitch Class 7, and ending on Pitch Class 0).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to key distance, several studies reported that transpositions to near keys (keys at nearby positions on the circle of fifths) are perceived as more similar to the original melody than are far-key transpositions (e.g., Cuddy, Cohen, & Mewhort, 1981;Cuddy, Cohen, & Miller, 1979;Takeuchi & Hulse, 1992;Trainor & Trehub, 1993). In addition, part of the results obtained in research Copyright 1996 Psychonomic Society, Inc. On the outside of the circle, key distance relative to the key of C major is presented.…”
Section: Similarity Judgments On Transposed Tonal Melodiesmentioning
confidence: 99%